Provisions of Gardening contract in Jurisprudence and Civil Code of Afghanistan. - Nael, Abdul Qader (Journal of Social Sciences - Kabul University, 2021)
Gardening contract shall mean giving tree and vine to another person for the purpose of nurturing and utilization in exchange for a specific part of its fruit. Gardening like any other contract has been legitimized in order to alleviate a part of social problems. While the general rules governing all contracts are applicable to the gardening contract, gardening also has its own elements, conditions, and provisions that must be observed. According to its two types, the legal effects of the gardening contract are divided into valid and vitiated. Gardening like other contracts may expose to vitiation due to some causes and factors, as a result, its provisions and effects become invalid.